Comparative Focal Mechanism and Fault Plane Ambiguity Analysis of the 2015 Gorkha Earthquake Using Global CMT and DMG Catalogs - Panth, Gaurav; Gyawali, Prajesh; Dhakal, Binaya Prasad; Panta, Ishwor (Journal of Advanced College of Engineering and Management, 2026)
On April 25, 2015, Nepal was struck by an Mw 7.8 earthquake. This study characterizes the source mechanism using focal mechanism solutions (beach balls) derived from the Global Centroid Moment Tensor (CMT) and Department of Mines and Geology (DMG) catalogs. The results confirm a thrust-faulting mechanism with strike, dip, and rake angles consistent with the regional tectonic framework. The rupture initiated near the hypocenter and propagated southeastward along the dip direction, a trajectory supported by finite-fault modeling. As no shallow surface rupture was observed, this rupture direction is supported by aftershock distribution, stereonet P-axis orientation, and finite-fault modeling studies. These findings improve understanding of rupture geometry and help identify potential seismic hazard zones in central Nepal.